Yeast mannan genetics controls the molecular specificity of anti-carbohydrate antibodies cross-reactive to the HIV envelope - Dunlop, D; Mansab, F; Doores, K; Zitzmann, N; Smith, D; Burton, D; Dwek, R; Scanlan, C (BioMed Central, 2009)
Immunologically self carbohydrates protect the human immunodeficiency virus type -1 (HIV-1) surface glycoprotein, gp120 from antibody recognition. However, one broadly neutralising antibody, 2G12, can protect against primary viral challenge by direct recognition of these "self" glycans on gp120.